2013
DOI: 10.2208/journalofjsce.1.1_162
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for Corrosion Cracking of Cover Concrete in Reinforced Concrete Structures

Abstract: This study was conducted to propose a simulation model for corrosion cracking of cover concrete in reinforced concrete structures located on land and subjected to airborne chloride. Chloride penetration has been known to have great influences on the design corroded mass due to the fact that it changes the corrosion initiating time and corrosion rate. Accordingly, a chloride penetration model was proposed for reinforced concrete structures located on land. This model was verified with the drawn core of concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A limit of the corrosion amount at which corrosion cracking occurs (d crack ), with a value ranging from 10 to 100 mg/cm 2 was proposed (JSCE 2007b;Piyamahant et al 2013;Takewaka and Matsumoto 1983), and it was reported that a value of 10 mg/cm 2 corresponded to a conservative estimation concerning the time of occurrence of corrosion cracking (JSCE 2007b). In addition, d crack was reported to increase with increase in the concrete cover thickness.…”
Section: Calculation Of Limit Of Reinforcement Corrosion Depthmentioning
confidence: 99%
“…A limit of the corrosion amount at which corrosion cracking occurs (d crack ), with a value ranging from 10 to 100 mg/cm 2 was proposed (JSCE 2007b;Piyamahant et al 2013;Takewaka and Matsumoto 1983), and it was reported that a value of 10 mg/cm 2 corresponded to a conservative estimation concerning the time of occurrence of corrosion cracking (JSCE 2007b). In addition, d crack was reported to increase with increase in the concrete cover thickness.…”
Section: Calculation Of Limit Of Reinforcement Corrosion Depthmentioning
confidence: 99%